2005
DOI: 10.1172/jci24471
|View full text |Cite
|
Sign up to set email alerts
|

Apoa5 Q139X truncation predisposes to late-onset hyperchylomicronemia due to lipoprotein lipase impairment

Abstract: While type 1 hyperlipidemia is associated with lipoprotein lipase or apoCII deficiencies, the etiology of type 5 hyperlipidemia remains largely unknown. We explored a new candidate gene, APOA5, for possible causative mutations in a pedigree of late-onset, vertically transmitted hyperchylomicronemia. A heterozygous Q139X mutation in APOA5 was present in both the proband and his affected son but was absent in 200 controls. It was subsequently found in 2 of 140 cases of hyperchylomicronemia. Haplotype analysis su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(115 citation statements)
references
References 45 publications
7
105
1
2
Order By: Relevance
“…In mice, adenoviral over expression of murine APOA5 resulted in a decreased production rate of VLDL triglycerides. Most importantly, as determined by APOB kinetic studies using stable isotopes Marcais et al have shown that the VLDL production rate was normal but the fractional catabolic rate of VLDL-APOB was decreased more than 20-fold in patients lacking normal APOA5 [26]. These and previously mentioned evidence demonstrate that APOA5 and ApoClll may have modulated the OxFA induced TG decreases.…”
Section: Resultsmentioning
confidence: 77%
“…In mice, adenoviral over expression of murine APOA5 resulted in a decreased production rate of VLDL triglycerides. Most importantly, as determined by APOB kinetic studies using stable isotopes Marcais et al have shown that the VLDL production rate was normal but the fractional catabolic rate of VLDL-APOB was decreased more than 20-fold in patients lacking normal APOA5 [26]. These and previously mentioned evidence demonstrate that APOA5 and ApoClll may have modulated the OxFA induced TG decreases.…”
Section: Resultsmentioning
confidence: 77%
“…In humans with hypertriglyceridaemia or familial combined hyperlipidaemia, polymorphisms in APOA5 show a strong association with plasma triglyceride levels across several ethnic groups [2][3][4]39]. ApoAV deficiency leads to severe hypertriglyceridaemia [40,41]. Recent measurements of plasma apoAV in normolipaemic subjects revealed a weak negative correlation [35,36] or a tendency towards a positive correlation of plasma apoAV and triglycerides (F. G. Schaap et al, unpublished results).…”
Section: Discussionmentioning
confidence: 96%
“…In humans, severe hyperchylomicronemia has been associated with mutations in the apolipoprotein AV (APOAV) gene [64]. ApoAV circulates at very low In the intestinal cell newly synthesized apoB48 follows one of two itineraries.…”
Section: Apolipoproteins and Chylomicron Synthesismentioning
confidence: 99%